A case of unplanned pregnancy at 2 months after uterine curettage in a patient with a hydatidiform mole. Issue 6 (June 2020) - Cao, Jie-Qiong; Zhao, Ye; Ma, Ying; Wang, Qiu-Man; Niu, Li-Na; Qiao, Si
Whether an unplanned pregnancy should be terminated during follow-up of a hydatidiform mole is controversial. We report a patient who had an unplanned pregnancy with a hydatidiform mole at 2 months after uterine curettage when the human chorionic gonadotropin level had decreased to a negative value. Hydatidiform mole was confirmed by histopathology. Uterine curettage was performed twice and regular follow-ups were performed after surgery. The patient achieved a full-term pregnancy. The Apgar score of the newborn was 10 at 1, 5, and 10 minutes, and the newborn had no malformations. We conclude that the pregnancy outcome might be good in an unplanned pregnancy when the human chorionic gonadotropin level is negative.